JURIDICAL ANALYSIS OF SANCTIONS TRESPASSER AGAINST NARCOTIC’S VICTIM BASED ON UTILITARIANISM JUSTICE VALUES - Andri Winjaya Laksana; Arpangi Arpangi (Jurnal Pembaharuan Hukum, 2019)
Utilirarisme have a basic philosophical principle or very firm stance that any fair punishment for wrongdoers must look further consequences. In law enforcement against narcotic crime, repressive efforts have been made ranging from arrest until the legal process in court. However, until now the number of drug abusers tend to increase. The public and law enforcement officers themselves, drug abusers are considered criminals who should be punished. Helpful punishment is punishment that brings meaning and positive value for the subject of the condemned, the general public and the potential criminals in society. Helpful punishment for violators of law that is deterring offenders, with the aim to create a future inmate subject better. By implementing a sentence of imprisonment to the victims of abusers of narcotics is an action that is not quite right, because a victim abusers of narcotics can be categorized as human physical and spiritual health problems, a sick person handling must be healed, and not send him to prison to collect the perpetrators of acts criminal